2011
DOI: 10.1111/j.1365-4632.2010.04743.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of idiopathic guttate hypomelanosis in 646 subjects and association with other aspects of photoaging

Abstract: It is very likely that IGH is a phenomenon associated with the skin's normal aging process and repeated microtrauma to skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 14 publications
2
54
2
1
Order By: Relevance
“…IGH is commonly seen in elderly patients with obscure etiopathogenesis and characterized by hypopigmented or depigmented macules and patches clinically. [3] Authors thought dermoscopy may fill this gap making the possibility of clinical diagnosis of IGH. Dermoscopy, a noninvasive, in vivo technique for the microscopic examination of pigmented skin lesions, has the potential to improve the diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…IGH is commonly seen in elderly patients with obscure etiopathogenesis and characterized by hypopigmented or depigmented macules and patches clinically. [3] Authors thought dermoscopy may fill this gap making the possibility of clinical diagnosis of IGH. Dermoscopy, a noninvasive, in vivo technique for the microscopic examination of pigmented skin lesions, has the potential to improve the diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that photoageing might be associated with IGH. Besides that, 85% of histopathological sections from their patients’ facial IGH lesions revealed mild degree of infiltration by mononuclear inflammatory cells localized in perivascular region of the upper dermis despite of non‐inflammatory clinical appearance of the skin lesions 1 . These findings were indicative of dermatoheliosis.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, IGH has been considered as a senile skin changes as its prevalence increases with age of patients 1,3 . A recent study from Shin et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations